Jual Beli Kondom Perspektif Hukum Islam - Rifqul ‘Afif; Ilham Candra (Saqifah: Jurnal Hukum Ekonomi Syariah, 2021)
This study aims to determine the perspective of Islamic law on buying and selling condoms and to explain the factors in selling contraceptives (condoms) to adolescents. The type of research is field research (Field Research) and data collection techniques are interviews. The results of the study, according to the perspective of Islamic law, buying and selling condoms is permissible if they are sold to married people, but buying and selling condoms is haram if they are sold to unmarried teenagers with the aim of connecting with couples who are not married. Factors Affecting the Occurrence of Condoms Buying and Selling Transactions for Teenagers: a) There is no governing law; b) Free association, lack of religious awareness; c) Modern Technology/Electronics; d) Insufficient parental care and supervisionl; e) Sexual stimulation; f) There is an opportunity from the government.